In vitro effects of particulate bone substitute materials on the resorption activity of human osteoclasts - G Russmueller; L Winkler; R Lieber; R Seemann; K Pirklbauer; C Perisanidis; B Kapeller; E Spassova; E Halwax; WP Poeschl; K Macfelda; D Moser (European Cells & Materials, 2017)
Much research has been done on bone cells, but only a few studies deal with biomaterial-induced effects on human osteoclasts, which may take on an important role in the successful regeneration of bone. In order to highlight such effects, human peripheral blood mononuclear cells (PBMCs) were extracted from venous blood, differentiated to osteoclasts and then cultured in, the presence of five particulate hydroxyapatite (HA)/β-tricalcium phosphate (TCP) biomaterials, on bovine bone slices and glass cover slips. The biomaterials, AlgOSS 50/50 (50 % HA/50 % TCP), AlgOSS 20/80 (20 % HA/80 % TCP), Algipore (98 % HA), Cerasorb (100 % TCP) and Bio-Oss (100 % HA) were chosen to assess their influence on cell morphology and numbers. Light microscopic evaluation was performed during ongoing cell culture. After 21 d of cultivation, the biomaterial-induced effects on osteoclastic resorption of the bone slices were evaluated by scanning electron microscopy (SEM). Osteoclast-like cells were identified by TRAP staining. All five biomaterials showed larger area fractions of resorbed bone than the control (5.6 ± 6.8 %), as measured on SEM images. The purely hydroxyapatite-based Algipore (9.8 ± 9.7 %) and Bio-Oss (7.9 ± 8.8 %) showed significantly elevated area fraction rates (p ≤ 0.05) of bone resorption. Light microscope evaluation revealed a significant, but inhibiting effect of Cerasorb (p = 0.05). These data indicated that introducing of small biomaterial hydroxyapatite particles may have improved the performance of bone substitute materials.